Challenges of Implementing a Project Management Methodology - BETHKE, JULIAN (My University, 2018)
In the business world of today global enterprises have to react quickly to new opportunities, challenges and demands in an international environment. To be prepared for those, Project Management is a key tool to enforce changes in an organisation. Making sure that these various projects will be completed successfully, the implementation of a Project Management Methodology is useful. In this way, a standardized approach for a better monitoring, controlling and reporting is used, as well as improved processes and best practices, to support the project managers in their work. In a case study the program of an IT provider of a large organisation is presented which is responsible for projects rolling out a virtual client for the whole organisation. On base of detected and identified problems, requirements were set on the to be implemented methodology. It is shown that all requirements could be achieved solving the problems which where existing before. In the theoretical framework it is analysed what kind of challenges there are, in regard of implementing, the content and barriers of using a methodology. After, an analysis takes place on base of the case study and theoretical background, considering all challenges which are taking place implementing a project methodology in an organisation. Thereby, it is always linked to the case study and theoretical background, analysing how the challenges were detected and could be solved. A developed challenge grid summarizes all challenges and is a suitable tool for being aware of the challenges when implementing a methodology. In the outlook the result of the developed challenge grid is used, showing that two challenges are not completely solved. It is recommended to deal with these problems by enhancing the methodology. Furthermore, an overall methodology for the whole IT provider is recommended, using the challenge grid. To summarize, the implementation of a methodology can only be successful if specific challenges are considered, evaluated and solved. The use of the challenge grid supports companies implementing such a methodology by presenting 10 main challenges in the area of implementation, content and organisational framework of a methodology. Therefore, this thesis contributes to project management research, enabling the implementation of methodologies in organisations by making aware what challenges there are and why. In this way, methodologies are might being used more often in organisations, increasing the probability of executing projects successfully.
Keywords: Samhällsbyggnadsteknik; Civil Engineering